Titanium dioxide nanoparticles obtained by sol gel method: Effect of the catalyst acids - Quintana, María (2010)
Titanium dioxide nanoparticles have been obtained by sol-gel process. Titanium isopropoxide was hydrolized in acidic medium at pH values between 0.5 and 1. The hydrolysis was catalyzed with HCl, HNO3 or HClO4, and studied their influence in the formation of titanium dioxide crystalline phases, i.e. rutile, anatase and brokite phases. The peptization process was studied with Visible and Fourier Transform Infrared (FTIR) spectroscopic techniques. Hydrothermal treatment at 220 °C for 12 hours permits the fabrication of well defined nanoparticles as it was observed by Transmission Electron Microscopy (TEM). The crystal structure was obtained by X-ray diffraction (XRD). Only the anatase phase was obtained using HClO4, however using HCl and HNO3 the anatase/rutile ratio is related to the pH of the initial acidic solution and the amount of anatase phase has increased when the pH of this solution increased. Some samples have traces of brokite phase.